Adaptation and attenuation of fowl adenovirus in mammalian cell line - Mohamed Sohaimi, Norfitriah; Bejo, Mohd Hair; Abdul Rahman, Omar; Ideris, Aini; Mat Isa, Nurulfiza (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
Highly pathogenic Fowl Adenoviruses (FAdVs) have been recognised as the primary pathogen of inclusion body hepatitis (IBH) in many poultry producing areas and thus, there is a need to develop vaccine for the control and prevention of the disease. It was the objective of the study to determine the adaptation and attenuation of FAdV (UPM1137) isolated from chickens with IBH in mammalian cell line (Vero cells). Confluent monolayer of Vero cells were inoculated with 0.1mL FAdV inoculum and monitored daily until day 7 post inoculation (pi) for cytopathic effect (CPE). CPE was recorded on day 6 pi on the first (P1) and subsequent passages up to passage 5 (P5). It was further confirmed that the CPE belong to FAdV by polymerase chain reaction (PCR) and sequence analysis. The virus successfully adapted and attenuated up to P5 with presence of amino acids changes. Phylogenetic trees revealed both samples from original homogenate embryo liver (P0) and P1 infected Vero cells (P1) were classified under FAdV group E strain (serotype 8). However, the FAdV at P5 could not be assigned to any clusters within groups as it might be due to a new strain of FAdV.